Attitude To Advertising As Its Social Effect - Petrová, Iva (Communication Today, 2025)
The article covers the attitude to advertising as the most dominant tool of marketing communication. Advertising and attitude to it certainly strongly inﬂuence the social behaviour and relationships between people. Here, we present the results of an empirical survey implemented on a selected group of respondents with secondary and university education under 50 years of age. The analysis presents dimensions and content namely of the affective component of this group’s attitude towards advertising. Advertising is perceived as part of the present life, as a necessary commonplace also with a number of negative connotations. The attitude of this group of people can be characterized as ambivalent with obvious elements of stylization; most of the respondents declare their own independence on advertising, they exclude their consumption behaviour and decision-making processes to be inﬂuenced by advertising.